Marriage and family relations as a structuring social practice of agents - Bernhard, Alena V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
Marriage and family relations have analyzed by means of theory of Structuration of A. Giddens in the article. The main provisions of this theory are considered through the prism of gender approach. Marriage and family are examined as the social practice reproduced by social agents. Dependence of marriage and family relations and certain sociocultural and socio-economic terms have viewed in the article. The definitions of the basic concepts of Structuration theory: structure, structuration, the routine, the duality of structure, rules, resources. The article describes the relationship between the routinized action and value orientations of individual and stages structuration of social practices.